MOTIVASI BELAJAR SISWA SMP SELAMA PEMBELAJARAN TATAP MUKA TERBATAS - Veny Imelinda Yusrin; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the learning motivation of Junior High School students during limited face-to-face learning, through survey. Research participants from VII – IX grade totaling 548 students with details of 50% of the number of students per grade level. The research instrument used was the Attention, Relevance, Confidence, Satisfaction (ARCS) learning motivation questionnaire, with a total of 20 statements. The data collection technique used was through questionnaires distributed online and during limited offline meetings using Google Forms. The results of this study were data on students learning motivation during limited face-to-face learning in the ARCS aspect, all of which are included in the good category. Although still in the good category, the ability of students to adapt to this limited face-to-face learning system still had low potential. Therefore, a more effective, creative, and innovative with using technology media and varied learning methods limited face-to-face learning evaluation is needed to increase students learning motivation during limited face-to-face learning.